2015
DOI: 10.12973/eurasia.2015.1416a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Topic Familiarity on Analogical Transfer in Problem-Solving: A Think-Aloud Study of Two Singular Cases

Abstract: We conducted a qualitative research of case studies based on think-aloud protocols. The aim was to carry out in-depth analyse secondary students' cognitive difficulties appearing in early stages of transfer processes in problem-solving. The task was to relate several source problems to a target problem, in order to solve it effectively. Source and target problems had different Surface and/or Structural similarities. In this paper, the solvers' high or low Familiarity with the problem stories on transfer proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
2
0
2
Order By: Relevance
“…However, many reports reporting think-aloud studies actually rely extensively on evidence from interviews or observation, or have investigated problem-solving involving dialogue between peers. Gomez Ferragud et al (2015) interviewed their subjects when investigating retrospective recall by paired learners. Millis (2012) studied thinking-aloud dialogue between learners as a form of active learning.…”
Section: For What Research Purposes Have the Think-aloud Approach Ormentioning
confidence: 99%
“…However, many reports reporting think-aloud studies actually rely extensively on evidence from interviews or observation, or have investigated problem-solving involving dialogue between peers. Gomez Ferragud et al (2015) interviewed their subjects when investigating retrospective recall by paired learners. Millis (2012) studied thinking-aloud dialogue between learners as a form of active learning.…”
Section: For What Research Purposes Have the Think-aloud Approach Ormentioning
confidence: 99%
“…They developed a model that can predict domain experts based on how they search for information. Gómez Ferragud, Solaz-Portolé s and Sanjosé [41] research also found a difference between expert and novice problemsolving ability. Liu, Liu and Belkin [6] affirm that users with different level of topic familiarity differ in their search behaviour.…”
Section: B Domain Knowledgementioning
confidence: 80%
“…Mahasiswa akan merasa kesulitan jika diberi permasalahan yang berbeda dari contoh yang diberikan oleh dosen. Siswa merasa kesulitan untuk menyaring permasalahan lain yang prosedur pemecahannya seharusnya berbeda dari permasalahan yang dicontohkan guru (Ferragud, Solaz-Portolés, & Sanjosé, 2015). Mahasiswa yang masuk di Program Studi Pendidikan Matematika harus paham dengan baik materi pada mata kuliah Geometri Analitik.…”
Section: Pendahuluanunclassified